Nilai Tukar Nelayan dan Perikanan di Kabupaten Probolinggo Tahun 2021 - Fatchur Rozci (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2022)
This study aims to measure the term of trade of fishermen and fish farmers, identify the level of income and expenditure of production as well as consumption of fishermen and fish farming, The population consists of fishing households in 7 sub-districts in Probolinggo Regency. The total household sample of Fishermen and Fish Farming was 147 fishermen, or an average of 21 Fishermen and Fish Farmers from each sub-district. The analysis method used is descriptive analysis, which is the analysis of qualitative and quantitative data, both primary and secondary data. The results of the analysis showed that the exchangeability of fishermen and fish farming products (NTNP) of 102.51 this shows that there is an increase in NTNP of 2.51 percent from the base year 2018. The increase was due to an increase in the price index received by fishermen and fish farming (It) by 7.60 percent in 2021 compared to the base year of 2018, and an increase in the price index paid by fishermen and fish farming (Ib) by 4.97 percent in 2021 compared to the base year 2018. NTNP of 102.51 shows that fishermen and fish farming in Probolinggo regency in 2021 are prosperous. The development of the level of income and expenditure of household consumption and the production costs of developing capital goods of fishermen and fish farming at the surplus position indicated by It of 107.60 and Ib of 104.97. This shows that the price received by fishermen and fish farming (It) is greater than the price index paid by fishermen and fish farmers (Ib) of Probolinggo regency in 2021.Keywords: Exchange Rate of Farmers, Fishermen, Fish Farmers, Prosperous